COMMUNICATION PROCESSES IN MAN’S SPIRITUAL SPHERE AND THEIR REFLECTION IN THE ROBINSONADE PHENOMENON - Sidorkina, Olena (Proceedings of the National Aviation University Series Philosophy Cultural, 2022)
Introduction. The versatility of meanings of the Robinsonade genre is manifested in the formulation of philosophical, ethical and sociopsychological issues of interaction and communication. In particular, attention is drawn to the communicative aspects of human existence in extreme conditions of forced isolation and the need to ensure survival in conditions of prolonged isolation from the usual society. The aimandtasks of this article are the analysis of the socio-philosophical aspects of communication processes in the spiritual sphere of an isolated person as a bearer of the entire set of social relations. Research methods. The methodological basis of this study is the theoretical foundations of the dialectical approach to the essence of contradiction, the unity of opposites and contradictions. Moreover, in our conclusions, we relied on the results of socio-philosophical studies of the spiritual sphere of society, the interaction of the public and the individual consciousness, in particular religious one, and philosophy of communication. Research results. Robinson’s communicativeactivity was carried out in the context of two groups of subjects of interaction: Robinson’s communicative interaction with the Supernatural and, at the appropriate stage of development of the novel plot, communicative interaction between Robinson and other people who represented a certain society for him through the prism of religious experience. At the same time, there is a combination of Robinson’s rationalism with deep religiosity, faith in God, and support for providence. Discussion. The communication process, Robinson’s constant socialization during the period of his solitary existence took place both through individual reflections and religious feelings, prayer communication with the God. The features of Robinson’s individual religious communication are embodied in real relationships with representatives of other cultures and religions, who in the given historical conditions were in a state of protracted conflicts. However, under conditions of similar existence and the need to solve common problems, simple and rational principles of coexistence are developed on the basis of universal values, helping to remove contradictions. Conclusion. In terms of the socio-philosophical aspects of communicative processes in the spiritual sphere of an isolated person, an important role belongs to man’s communication with the environment, the Supernatural and from and to himself (“auto communication”). Robinson described by D. Defoe managed to establish such a constructive dialogue, an important component of which was the character’s religious consciousness, its development and transformation, which reflected the process of his spiritual formation in the novel.